Subsídios para o Programa de Monitoramento e Gestão do Uso Público do Parque Natural Morro do Osso, Porto Alegre, RS. - Nascimento, Cristina Alves (2018)
The Morro do Osso Natural Park is a Conservation Unit located in the middle of the intense urbanization of Porto Alegre, capital of the state of Rio Grande do Sul. The area is rich in conserved environments and of fundamental importance for the native flora and fauna, being open to visitation. However, there are no studies dealing with the impacts that this current and past use causes on the trails. Considering this, this study aimed to generate subsidies for the elaboration of the Public Use Monitoring and Management Program of the area, with the specific objectives of characterizing the visitor profile and the visitors of its Environmental Education Trail and evaluating impact indicators of public use in the their trails. Were analyzed the Park Service records, between 2006 and 2015, and applied 125 questionnaires, between June 2015 and May 2016. he area has seen a significant increase in the number of visitors scheduled in the last decade, ranging from 693 in 2006 to 2,114 in 2015. The main category of visitors was educational institutions, predominantly of fundamental level and public. The visitors are mostly female and under 15 years old, being characterized as elementary school students. They live in Porto Alegre, but they visit the area for the first time, usually with their educational institution, the main source of publicity of the Park. Cultural and educational activities are the most practiced, evidencing the link of the actions developed in the trail with the formal Environmental Education. In addition, between June 2015 and June 2016, the determination initial monitoring and evaluation of effectiveness of use of four indicators in the Park: solid residues, trail width, visible erosion and unofficial trails. The solid residues, visible erosion and unofficial trails indicators presented low standards on both trails. The trail width was normal on the Fonte Trail and big on the Eixo Central Trail. No indicators were corrected by the number of visitors. The trail width and visible erosion indicators sented correlation with climatic factors. It was therefore concluded that possibly the public use of the Park is not generating significant impacts on its trails, so that the conservation of the environment is being maintained through the resilience capacity of the ecosystem itself. It is suggested that the impacts monitoring used in this study be maintained, being the survey presented here defined as the initial monitoring of the Monitoring and Public Use Program of the Morro do Osso Natural Park.. The visitation management proved to be a good example at the national level, given the existence of detailed historical data, an interpretative interpretive script and management actions to mitigate negative impacts. However, the need to characterize the profile and perceptions of visitors of whole Park, important to understand the potentialities and problems of the area. It is suggested that the impacts monitoring used in this study be maintained, being the survey presented here defined as the initial monitoring of the Monitoring and Public Use Program of the Morro do Osso Natural Park. Thus, these results will serve as subsidies for future actions of public use of the Park.